Proceedings of the 2019 on Creativity and Cognition 2019
DOI: 10.1145/3325480.3325484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Digital Creativity Support by Journalists in Newsrooms

Abstract: This paper reports the evaluation of a new digital support tool designed to increase journalist creativity and productivity in newsrooms. After outlining the tool's principles, interactive features and architecture, the paper reports the installation and use of the tool over 2 months by 12 journalists in the newsrooms of 3 newspapers. Results from this evaluation revealed that tool use was associated with published news articles rated as more novel but not more valuable than published articles written by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The use of a 3-tier architecture has enabled cost-effective adaptation of the tool for use in different settings: the distinct interface layer has enabled new versions of INJECT to be delivered quickly for different text editor and web application environments; the separate application layer has been enabled these new versions of INJECT to have most if not all of the reasoning and interaction capabilities of INJECT at launch; and the separate data layer has enabled configurations of the INJECT tool to manipulate news and social media information from different private and public sources and written in different languages. Early evaluation of INJECT [14] by a limited number of journalists revealed that the tool was effective in supporting journalists discover new and useful angles on stories written with INJECT's support, often quickly. However, the tool has been more effective when extended existing storylines rather than developed new ones.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a 3-tier architecture has enabled cost-effective adaptation of the tool for use in different settings: the distinct interface layer has enabled new versions of INJECT to be delivered quickly for different text editor and web application environments; the separate application layer has been enabled these new versions of INJECT to have most if not all of the reasoning and interaction capabilities of INJECT at launch; and the separate data layer has enabled configurations of the INJECT tool to manipulate news and social media information from different private and public sources and written in different languages. Early evaluation of INJECT [14] by a limited number of journalists revealed that the tool was effective in supporting journalists discover new and useful angles on stories written with INJECT's support, often quickly. However, the tool has been more effective when extended existing storylines rather than developed new ones.…”
Section: Discussionmentioning
confidence: 99%
“…INJECT [43,44] supported story creation through creative idea generation by using machine learning and NLP to extract terms from a partially-written story. It then used the extracted terms to search news sources for existing stories to inspire the in-progress story.…”
Section: Existing Algorithmic Systems For Journalistsmentioning
confidence: 99%
“…The AI cards were designed in response. The AI cards were inspired by existing algorithmic journalism tools [11,20,43,44,65] (see section 2.3).…”
Section: Value Cardsmentioning
confidence: 99%
See 2 more Smart Citations